Changing paradigm for data, economy, and ownership in the digital era - Zhelezniak, Tanya (Henry Stewart Talks, 2023)
Cryptocurrency, Blockchain, Management strategy, Technology, Open innovation, Digital economy, Walmart, EthicHub